(untitled) (Zoological Records and Reviews, 2024)
Effective wildlife conservation depends fundamentally on the quality, coherence, and implementation of conservation policies at local, national, and international scales. Europe’s multilevel conservation policy architecture – encompassing the EU Habitats Directive, Birds Directive, CITES, the Bern Convention, and national species action plans – represents one of the most comprehensive regulatory frameworks for wildlife protection globally, yet persistent implementation gaps, funding shortfalls, and cross-border coordination failures continue to undermine conservation outcomes for many priority species. This review synthesises evidence from 186 primary studies (2005-2024) examining the effectiveness, compliance, and policy design features of wildlife conservation frameworks in European contexts. Policy effectiveness was evaluated across five dimensions: legal stringency, implementation consistency, enforcement capacity, adaptive management provisions, and cross-border coordination mechanisms. The EU Habitats Directive’s Article 17 reporting cycle – assessing favourable conservation status for Annex II species every six years – provides the most systematic pan-European evidence base for policy outcome evaluation, with the most recent 2019 assessment reporting only 15% of assessed species in favourable status. Key policy design features associated with improved conservation outcomes include: species-specific action plans with quantified targets, dedicated funding mechanisms, independent monitoring, and transboundary management agreements. Emerging policy instruments – biodiversity net gain requirements, payment for ecosystem services, and the EU Nature Restoration Law – are evaluated for their potential to address persistent implementation gaps. A framework for evidence-based wildlife policy evaluation and reform is presented.